Older adult solitary drinking: associations with subjective and objective cognitive functioning - Skrzynski, Carillon J.; Bryan, Angela D. (Frontiers in Aging Neuroscience, 2026)
BackgroundSolitary drinking is a pattern of hazardous alcohol consumption that is problematic at any age but is more prevalent in older adults, yet most research focuses on younger samples. Research on solitary drinking and cognition is critical as older adults are more vulnerable to cognitive decline, and cognitive decline is increased by hazardous drinking.MethodsUsing data from a larger project, the present study explored relationships between cognitive function and solitary drinking among 342 individuals 60 + years old (55.56% Female, 89.47% White). Solitary drinking, objective cognition via the Rey Auditory Verbal Learning Test (Rey), and subjective cognition via the Functional Assessment of Cancer Therapy-Cognitive Function (FactCog) questionnaire were assessed at baseline. The FactCog was also completed at a 4-month assessment.ResultsMore frequent solitary drinking was correlated with poorer Rey scores and worse scores on the FactCog subscales Perceived Cognitive Abilities (PCA) and Perceived Cognitive Impairment (PCI; ps < 0.05) among older adults who drank alcohol. Older adults who drank alcohol only in social situations had significantly higher baseline Rey learning scores compared to those who did not drink (p = 0.04) and higher delayed Recall scores compared to those who drink while alone (p = 0.03). They also had significantly higher baseline PCI scores compared to the combined pool of solitary and non-drinking individuals (p = 0.046). Finally, PCI averaged across baseline and 4 months was better among the social-only versus solitary drinking group (p = 0.03).ConclusionOur results expand knowledge of solitary drinking in older adulthood by connecting it to poorer objective and subjective cognitive function.